Fertilization of Food Waste Management in UTHM’s Cafeteria Using Arduino - Rusli, Muhammad Hafiz Daniel; Hashim, Hairulazwan (Progress in Engineering Application and Technology, 2021)
Everyday food is consumed by humans for survival and basic needs for daily consumption. When humans eat food, there will be waste such as unfinished food or bones. With increasing food waste on earth, it can cause many kinds of diseases if the waste is not managed properly. Tons of food waste are created yearly on earth. To overcome the food waste problem, composting was introduced so we can recycle the food waste into compost fertilizer that can help improve soil nutrition. This research paper presents an overview of Fertilization of Food Waste Management in UTHM’s Cafeteria. This project aims to produce compost fertilizer within a shorter time. The machine will preserve the food waste and let it decompose by letting good bacteria eat the waste. The machine will create an optimum temperature so that the microorganism can live and decompose food waste into fertilizer. Temperature and moisture are monitored during the decomposition of food waste. With the help of this machine, food wastage that produces daily can be reduced. Different kinds of pollution and sickness can also be reduced so that humans can live in a healthy world.